(untitled) (Applied Sciences in Dentistry, 2021)
Background: Permanent teeth avulsion represents a high rate among all dental trauma injuries and their rapid management is very important for prognosis. The aim of the present study is to report the multidisciplinary treatment and 13-years follow-up of a case of the replantation of a permanent maxillary central incisor after dental avulsion. Clinical presentation: A 8-year-old male patient presenting avulsion of right maxillary central incisor (11) and subluxation associated with uncomplicated crown fracture of left permanent central incisor (21) was treated with immediate replantation of the #11. Due to anterior open bite, severe crowding of teeth in the trauma region and Angle’s Class II profile, an orthodontic approach was performed. Long-term follow-up at 12-years after the trauma, and 7-years after the beginning of orthodontic treatment, appliance was removed, and permanent root canal filling of right maxillary central incisor was performed. Clinical Relevance: The treatment of choice for a dental avulsion is to replant the tooth as soon as the trauma has occurred for a better prognosis, addressing the guidelines of the International Association of Dental Traumatology (IADT) associated with orthodontic management. Conclusion: Clinical results after 13-years follow-up showed that this approach controlled the progressive resorption and allowed orthodontic movement maintained the patient’s health over time.